1997
DOI: 10.1023/a:1018470208730
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Hybrid plants and animals often show suppression of activity of ribosomal genes (rDNA) originating from one of the parental or ancestral species. In the wheat x rye amphiploid triticale, containing 28 chromosomes of wheat origin and 14 from rye, rDNA of rye origin (on chromosome 1R) is not normally expressed, while the 1B- and 6B-origin rDNA from wheat shows strong expression. Expression of rDNA can be accurately assessed by the silver staining method, which stains both interphase nucleoli and metaphase rDNA s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
22
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(23 citation statements)
references
References 17 publications
1
22
0
Order By: Relevance
“…Another possibility is that aza-dC and histone deacetylase inhibitors derepress silenced rRNA genes by activating a regulatory locus that controls the transcriptional competence of the NOR. Involvement of other loci is consistent with studies showing loss of nucleolar dominance because of chromosome substitution in wheat and triticale (18,36) or because of chromosome rearrangements in Drosophila (38) and barley (47). Our current study suggests that such hypothetical regulatory loci are unlikely to encode species-specific transcription factors.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Another possibility is that aza-dC and histone deacetylase inhibitors derepress silenced rRNA genes by activating a regulatory locus that controls the transcriptional competence of the NOR. Involvement of other loci is consistent with studies showing loss of nucleolar dominance because of chromosome substitution in wheat and triticale (18,36) or because of chromosome rearrangements in Drosophila (38) and barley (47). Our current study suggests that such hypothetical regulatory loci are unlikely to encode species-specific transcription factors.…”
Section: Discussionsupporting
confidence: 90%
“…An effect of genome dosage on the number of nucleoli visible at interphase in allopolyploid Ribes (gooseberry and black currant) hybrids was reported, suggesting that dominance could be overcome by increasing the number of underdominant NORs (35). Studies in wheat have shown also that NOR activity is variable in different chromosome addition lines, suggesting that genes unlinked to the NORs can affect their activity (18,36). However, the demonstration that normally dominant rRNA genes can be made underdominant is unprecedented.…”
Section: Discussionmentioning
confidence: 99%
“…The latter studies have also shown that plasmid-borne rRNA genes can be efficiently transcribed in hybrid cells in which their endogenous chromosomal counterparts are repressed, indicating that nucleolar dominance is strictly a chromosomal phenomenon (17). Chromosome rearrangements that move NORs to new chromosomal environments, or that delete sequences adjacent to NORs without altering rRNA gene sequences, can also induce or negate nucleolar dominance (18)(19)(20)(21). Collectively, these data suggest that the chromosomal context of an NOR is an important determinant of nucleolar dominance, for reasons that are currently unknown.…”
mentioning
confidence: 97%
“…the changes in chromatin organization are of great importance for the control of rRNA gene repression in inter-specific hybrids (12,16,24). one could expect that the same epigenetic mechanisms may also be involved in differential expression of the noRs in cytologically reconstructed barley karyotypes.…”
Section: Introductionmentioning
confidence: 99%